Trojaka priroda romantičkog sjećanja : slučaj Williama Wordswortha - Domines Veliki, Martina (Array, 2014)
The article deals with William Wordsworth as the first English Romantic poet who questions the onto-logical priority of the object of perception and insists upon the poet's subjective response to the outward world. In that way, Wordsworth's poetry gives voice to a movement from the object of perception to the perceiving subject registered in the empirical philosophy of John Locke and David Hume before the Co-pernican turn of Kantian thought. In his Preface to Lyrical Ballads (1800) Wordsworth says that poetry is "a spontaneous overflow of powerful feelings", emphasizing the subjective nature of the Romantic experience. Therefore, M.H. Abrams would insist on the direct dialogue between the poet's mind and the surrounding nature which, in the criticism after WWII, is seen as the main topos of Romantic literature. However, the article argues that the idea of such direct Romantic experience of nature is a fallacy and only one topos among many, as the recollection of the primary experience becomes more important than the experience itself. By stressing the importance of memory in the creation of the Romantic self and the role played by language as the recollected experience has to be written down, the article explores the dynamics between past and present experiences both in Wordsworth's poetry and in traditional and post-structuralist readings of his poetry.